2005
DOI: 10.21273/hortsci.40.4.1133a
|View full text |Cite
|
Sign up to set email alerts
|

Wool and Hair Waste as Nutrient Source for High-value Crops

Abstract: One small-plotfield and five container experiments were conducted to evaluate sheep wool-wastes and human hair-wastes as soil amendments and nutrient sources for high-value crops. Overall, the wool-waste or hair-waste addition to soil: 1) increased yields from basil, garden sage, peppermint, valerian, thorn apple, marigold, foxglove, and swiss chard; 2) increased the amount of secondary metabolites (such as essential oils and alkaloids); 3) increased NH4-N and NO3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Wool acidifies soil, thus improving the pH for many garden and greenhouse crops, and it improves the water-holding capacity of soil in potted plants (Poston et al 2005) because of its hygroscopicity (Zoccola et al 2009). Wool also contains essential plant nutrients (Gershuny and Martin 2018), decomposes slowly, and acts as a slowrelease sulfur, nitrogen, phosphorous, and potassium fertilizer under field or greenhouse conditions (Zheljazkov et al 2005) and for potted plants (Poston et al 2005).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Wool acidifies soil, thus improving the pH for many garden and greenhouse crops, and it improves the water-holding capacity of soil in potted plants (Poston et al 2005) because of its hygroscopicity (Zoccola et al 2009). Wool also contains essential plant nutrients (Gershuny and Martin 2018), decomposes slowly, and acts as a slowrelease sulfur, nitrogen, phosphorous, and potassium fertilizer under field or greenhouse conditions (Zheljazkov et al 2005) and for potted plants (Poston et al 2005).…”
mentioning
confidence: 99%
“…It has been suggested that the addition of wool at 3.3 gÁkg À1 of soil may support two to five harvests under greenhouse conditions and two to four seasons under field production conditions (Zheljazkov et al 2005). However, raw wool contains impurities such as detergents and pesticides (Pearson et al 2004) that could contaminate compost and soils (Fong et al 1951).…”
mentioning
confidence: 99%
See 2 more Smart Citations